Compensatory Guaiacyl Lignin Biosynthesis at the Expense of Syringyl Lignin in 4CL1-Knockout Poplar . Issue 1 (6th March 2020) - Tsai, Chung-Jui; Xu, Peng; Xue, Liang-Jiao; Hu, Hao; Nyamdari, Batbayar; Naran, Radnaa; Zhou, Xiaohong; Goeminne, Geert; Gao, Ruili; Gjersing, Erica; Dahlen, Joseph; Pattathil, Sivakumar; et al.
Abstract : Knocking out a lignin-associated gene in poplar reveals a compensatory pathway for lignification with links to thiol redox balance and sulfur assimilation. Abstract: The lignin biosynthetic pathway is highly conserved in angiosperms, yet pathway manipulations give rise to a variety of taxon-specific outcomes. Knockout of lignin-associated 4 - coumarate : CoA ligases ( 4CLs ) in herbaceous species mainly reduces guaiacyl (G) lignin and enhances cell wall saccharification. Here we show that CRISPR-knockout of 4CL1 in poplar ( Populus tremula × alba ) preferentially reduced syringyl (S) lignin, with negligible effects on biomass recalcitrance. Concordant with reduced S-lignin was downregulation of ferulate 5 - hydroxylases ( F5Hs ). Lignification was largely sustained by 4CL5, a low-affinity paralog of 4CL1 typically with only minor xylem expression or activity. Levels of caffeate, the preferred substrate of 4CL5, increased in line with significant upregulation of caffeoyl shikimate esterase1 . Upregulation of caffeoyl - CoA O - methyltransferase1 and downregulation of F5Hs are consistent with preferential funneling of 4CL5 products toward G-lignin biosynthesis at the expense of S-lignin. Thus, transcriptional and metabolic adaptations to 4CL1 -knockout appear to have enabled 4CL5 catalysis at a level sufficient to sustain lignification. Finally, genes involved in sulfur assimilation, the glutathione-ascorbate cycle, and various antioxidant systems were upregulated in the mutants, suggesting cascading responses to perturbed thioesterification in lignin biosynthesis.